Development and Validation of the "Tübingen Inventory to Measure Teachers' Profession-Specific Value Orientations" (TIVO) - Samuel Merk; Martin Drahmann; Colin Cramer (SAGE Publishing, 2021)
Broadly understood, values represent orientation guidelines for daily action, thinking, and feeling. Thus, they affect teachers' everyday work and are among their professional competencies. While general values and some single profession-specific values of teachers (e.g., responsibility) have already been investigated empirically, the current study aims to cover a broader range of profession-specific values by developing and validating the Tübingen Inventory to Measure Teachers' Profession-Specific Value Orientations (TIVO), based on three independent studies with pre-service (Studies 1 and 2; N 1 = 334, N 2 = 239) and in-service teachers (N 3 = 308). The results demonstrate that the TIVO is appropriate to assess four profession-specific values in a second-order model: caring, justice, responsibility, and truthfulness as first-order factors, with fairness as a second-order factor loading on the latter three first-order factors. The results from preregistered experiments and confirmatory factor analysis provide consistent evidence for the construct validity of the TIVO.